Optimization of Aeration Technique for the Reduction of Impurities (Corrosive Gases) from Biogas - Sujan, SMA; Bashar, MS; Rahaman, M; Haque, MN; Miah, MY; Jamal, MS; Banik, SK (Bangladesh Journal of Scientific and Industrial Research, 2011)
Biogas, produced from organic waste through anaerobic digestion (AD), is mainly composed of methane (CH4) and carbon dioxide (CO2) with smaller amount of hydrogen sulfide (H2S) and nitrogen (N2). Trace amount of some other gases are occasionally present in biogas. For electricity generation from biogas, reduction of H2S is necessary because it is toxic and corrosive to most of the equipments. Reduction of Hydrogen Sulfide (H2S) from poultry based biogas (normally it contents 1500 2500 ppm) can be done by dosing air/oxygen to the main digester during the digestion process. Two methods of air injection technique have been followed for optimization of the process. Firstly two hour interval air injection and secondly air injection based on percentage of hourly gas production. The optimum air percentage to minimize H2S should be at least 3.00%. After aeration H2S level comes to the desired level (<50ppm) within 1.5-2.0 hours and remains constant up to 7-9 hours and biogas can be used for effective power generation. A complete aeration system has been developed which is simple and cost effective for H2S reduction to the desired level from poultry based biogas plant. This system can be applied for any size of poultry based biogas plant for effective power generation. Key words: Anaerobic digestion; Hydrogen Sulfide (H2S); Aeration; Biogas digester; Power generation DOI: http://dx.doi.org/10.3329/bjsir.v46i3.9040 BJSIR 2011; 46(3): 339-342